Thermal degradation of brick made of soil and cassava wastewater - Araújo, Narcísio Cabral de; Queiroz, Abílio José Procópio; Ramos, Alana Pereira; Santos, Renato Correia dos; Buriti, Josué da Silva; Gomes, Antônia Araújo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The objective of this research was to evaluate the thermal degradation of brick made from red clay and cassava wastewater. The analyzes were performed following the methods of thermogravimetry (TG) and differential scanning calorimetry (DSC), which were repeated using conventional bricks for comparative evaluation of the results to different reasons and heating. Thesamples comprised 92% of clay and 8% water (AA) and 92% of clay and 8%cassava wastewater (AM) had lower thermal stability, with an average loss of 7.93% mass degradation occurring between room temperature and 1000 °C, being visible and acceptable state that occur in three stages associated with the loss of volatilization ofsolvents, most AA, and burning the organic material, for AM most especially, as well as the oxides formed during the process. DSC curves were identified by an endothermic reaction associated with the first mass loss, and two reactions in the intermediate region of the curve, an endothermic and an exothermic connected the second bereavement